Novel cultural experiences for the communication of museum collections: the Francesco Fichera projects fund at Museo della Rappresentazione in Catania - Mariateresa Galizia; Graziana D'Agostino; Raissa Garozzo; Federico Mario La Russa; Gaetano Seminara; Cettina Santagati (Disegnare con)
The paper illustrates the strategies set up for the communication of the documentary heritage of the Museum of Representation (Mu.Ra.), Department of Civil Engineering and Architecture, University of Catania. Mu.Ra. houses and exhibits the collections of architectural projects (Francesco Fichera Archive) and chalcographies (including the collection of G.B. Piranesi). The mission of the museum is to preserve, protect and make available to the scientific as well as to a wider community, the results of the Department research, education and dissemination activities. This has inspired a new way of thinking, valuing and using the heritage possessed. Focusing on the enhancement of the collections and merging research and educational purposes, an innovative participatory approach has been investigated and experimented. Indeed the students of the drawing courses and interns at the museum have been involved in their dual role of future designers and potential visitors of the museum developing strategies for new target users. Specifically, the experimentation was carried out on the projects by Francesco Fichera and was focused on the development of a communication strategy addressed to the reading and understanding of the architectural project. The aim was to actively involve the visitor in the learning process, making the visit a cognitive and emotional experience through new forms of representation. To achieve this goal the students worked both on architectures existing in Catania and on the unrealized projects, with the aim of recreating, using 3D modeling, virtual environments and reality, the visual and perceptive sensations of the unfinished architectural space. DOI: https://doi.org/10.20365/disegnarecon.23.2019.8